8 researchers, 2 varsities lauded for achievements - Rozana, Sani (The New Straits Times Press (M) Bhd., 2019)
EIGHT academics and two universities were feted as the country’s most promising and influential in research at the Malaysia Research Star Awards (MRSA) 2019 in Putrajaya last week.